2010
DOI: 10.1007/s10592-010-0119-3
|View full text |Cite
|
Sign up to set email alerts
|

MHC-mediated local adaptation in reciprocally translocated Chinook salmon

Abstract: Most Pacific salmonid populations have faced significant population declines over the past 30 years. In order to effectively conserve and manage these populations, knowledge of the evolutionary adaptive state of individuals and the scale of adaptation across populations is needed. The vertebrate major histocompatibility complex (MHC) represents an important adaptation to parasites, and genes encoding for the MHC are widely held to be undergoing balancing selection. However, the generality of balancing selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 57 publications
4
34
0
Order By: Relevance
“…In addition to body mass, heterozygosity also positively influenced the survival of female Black Grouse. This is similar to the findings of many other studies where genome-wide heterozygosity and heterozygosity at specific loci have been associated with increased survival in some vertebrate species [mammals (Banks et al 2010;Forcada and Hoffman 2014); fish (Evans et al 2010); birds (Worley et al 2010;Cézilly et al 2016)]. Similar to body size, the relationship between survival and heterozygosity has been mainly found in juveniles (e.g.…”
Section: Discussion Heterozygosity and Fitnesssupporting
confidence: 90%
“…In addition to body mass, heterozygosity also positively influenced the survival of female Black Grouse. This is similar to the findings of many other studies where genome-wide heterozygosity and heterozygosity at specific loci have been associated with increased survival in some vertebrate species [mammals (Banks et al 2010;Forcada and Hoffman 2014); fish (Evans et al 2010); birds (Worley et al 2010;Cézilly et al 2016)]. Similar to body size, the relationship between survival and heterozygosity has been mainly found in juveniles (e.g.…”
Section: Discussion Heterozygosity and Fitnesssupporting
confidence: 90%
“…It has been suggested that the MHC class II confers local adaptation in Chinook salmon (Evans et al, 2010). Our findings suggest that the low MHC class II diversity found in this and other Chinook salmon populations Evans et al, 2010) could be maintained via CFC, possibly to preserve adaptation to the parasite community at the spawning ground.…”
Section: The Mhc and Fertilization Successmentioning
confidence: 60%
“…This variation could not be attributed to the MHC class I either. In contrast, MHC class II, which possibly plays a role in local adaptation (Evans et al, 2010), appears to be a significant driver of non-random gamete fusion in Chinook salmon. Since Chinook salmon are strongly adapted to their breeding ground, which is known to complicate the supplementation of endangered populations (Taylor, 1991), the MHC class II-based CFC could potentially be considered in targeted supportive breeding programs to augment and conserve endangered salmon populations.…”
Section: The Mhc and Fertilization Successmentioning
confidence: 85%
See 1 more Smart Citation
“…Members of the salmonid family cover a wide range of different life-history strategies (Hutchings and Morris 1985;Crete-Lafreniere et al 2012) and ecological conditions (e.g., Maret et al 1997;Evans et al 2010Evans et al , 2012Hecht et al 2012). Symbiotic microbes may to a large degree reflect these ecological conditions.…”
Section: Discussionmentioning
confidence: 99%